INFLUENCE OF PAST CROPS ON WINTER WHEAT YIELD - Qutlimuratova Dilfuza Baltabaevna (European Journal of Agricultural and Rural Education, 2022)
In the saline soils of the Republic of Karakalpakstan, field experiments were conducted to determine the effect of past crops (mung bean, sesame, soybean), which were included in the system of short-term crop rotation (1: 2, cotton: grain: grain) and sown before winter wheat, on winter wheat yields. In the experiment, it was found that the yield was 9-12 q / ha higher than all other methods when mung bean was sown for grain before winter wheat as a past crop, then as an interval crop (mung bean) and fertilized with an additional 20 t / ha and then winter wheat was sown